Discussion of functional dyspepsia issue in American gastroenterological week reports (Orlando, 2013) - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
The aim of review. To discuss the reports on functional dyspepsia (FD), presented at the American gastroenterological week (Orlando, May 18-20, 2013).Key points. Of all etiological factors of FD the major attention is paid to hereditary predisposition, pattern of nutrition, bad habits (smoking), past food toxicoinfection, psychological and social factors. Frequent combination of FD to other gastro-intestinal functional diseases (most notably — irritable bowel syndrome), as well as to gastroesophageal reflux disease is marked. Treatment of FD includes application first of all of proton pump inhibitors, prokinetics, antidepressants and selective serotonin reuptake inhibitors.Conclusion. Pathophysiological and clinical aspects of FD require further studying.